The roles of autophagy and mitophagy in corneal pathology: current knowledge and future perspectives - Ayilam Ramachandran, Rajalakshmy; Sanches, Jose Marcos; Robertson, Danielle M. (Frontiers in Medicine, 2023)
The cornea is the clear dome that covers the front portion of the globe. The primary functions of the cornea are to promote the refraction of light and to protect the eye from invading pathogens, both of which are essential for the preservation of vision. Homeostasis of each cellular layer of the cornea requires the orchestration of multiple processes, including the ability to respond to stress. One mechanism whereby cells respond to stress is autophagy, or the process of “self-eating”. Autophagy functions to clear damaged proteins and organelles. During nutrient deprivation, amino acids released from protein breakdown during autophagy are used as a fuel source. Similarly, mitophagy, a selective form of autophagy, functions to clear damaged mitochondria. Thus, autophagy and mitophagy are important intracellular degradative processes that sustain tissue homeostasis. Importantly, the inhibition or excessive activation of these processes results in deleterious effects on the cell. In the cornea, impairment or inhibition of these mechanisms have been associated with corneal disease, degenerations, and dystrophies. This review summarizes the current body of knowledge on autophagy and mitophagy at all layers in the cornea in both non-infectious and infectious corneal disease, dystrophies and degenerations. It further highlights the critical gaps in our understanding of mitochondrial dysfunction, with implications for novel therapeutics in clinical practice.